Primary Squamous Cell Carcinoma of the Ampulla of Vater - Bolanaki, Helen; Giatromanolaki, Alexandra; Sivridis, Efthimios; Karayiannakis, Anastasios J (JOP. Journal of the Pancreas, 2014)
Context Squamous carcinoma of the ampulla of Vater is a very rare tumor with only three cases been reported so far. Case report Here, we report the case of a 68-year-old man who presented with painless obstructive jaundice, general fatigue, loss of appetite and weight loss. Laboratory tests revealed hypochromic anemia. Total and direct bilirubin, alkaline phosphatase, liver enzymes, carbohydrate antigen 19-9 (CA 19-9) and carcinoembryonic antigen (CEA) were all elevated. Abdominal ultrasonography and computed tomography showed a distended gallbladder, dilatation of the intra- and extra-hepatic bile ducts and enlargement of the pancreatic head. Endoscopic retrograde cholangiopancreatography revealed a bulging papilla with infiltrative growth at the ampulla of Vater but endoscopic biopsies were inconclusive. The patient was treated with classical Whipple’s pancreaticoduodenectomy. Histopathological examination showed a moderately differentiated squamous cell carcinoma. Multiple serial sectioning of the tumor specimen failed to detect an adenomatous component. Regional lymph nodes and resection margins were free of tumor and the disease was classified as stage IIA (T3N0M0) according to the TNM system. Adjuvant treatment was not given. Despite curative resection, multiple liver metastases developed after four months and the patient succumbed to progressive hepatic failure 5 months after the operation. Conclusion Primary pure squamous cell carcinoma of the ampulla of Vater is a very rare histological type of carcinoma. Clinical characteristics and optimal treatment are obscure. Primary surgical treatment with curative intent should be performed although this type of carcinoma associates with dismal prognosis. Image: Gray-white tumor tissue located within the wall of the ampulla of Vater.